Stability study of cypermethrin towards high surface area calcium oxide - 263309 Wong, Ka Lun (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Science with Education (Chemistry)) - Universiti Teknologi Malaysia, 2004